Modelling the relationship between emotional intelligence, transformational leadership and job performance among public school leader in Malaysia - Nurul Hudani Md. Nawi; Ma'rof Redzuan; Hanina Hamsan; Balan Rathakrishnan; Sreehari Ravindranath (Global Journal For Research Analysis (GJRA), 2015)
This explanatory study tested a model within individual context the relationship among emotional intelligence, transformational leadership behaviour as well as the impact towards job performance. A total of 306 respondents i.e 132=Male; 174=Female from the educator leader in High School Performance (SBT) was participated in this study. Using a structured questionnaire consist of three sets of questionnaires in order to measure emotional intelligence (Emotional Competence Inventory) (ECI), transformational leadership behaviour (Multi-factor leadership questionnaire) (MLQ) and job performance were administered. The model was tested using Structural Equation Modelling; an acceptable level of model fit was found. It shows that the model fit indices demonstrate TLI (Tucker-Lewis Index), NFI (Normed Fit Index), RFI (Relative Fit Index), IFI (Incremental Fit Index) and CFI (Comparative Fit Index) are more than .90 (from .941 until .979), RMSEA (Root Mean Square Error of Approximation) also shows 0.070 (RMSEA <. 08) (Byrne, 2001). These values indicate an adequate fit and it’s obviously met the basic requirement of model fit. The values of the Chi-Squared Roots Goodness of Fit also show 2.509, below 3. Therefore, the model is significantly fit and supports the data. SEM analysis shows that emotional intelligence is positively related to transformational leadership behaviour, and transformational leadership behaviour has a significant and positive relationship with job performance. On a practical note, the assessment of psychological constructs in school setting eg; EQ and leadership behavior could possibly assist in enhancing the work performances in delivering huge benefits to the society especially in the educational contexts.